Estimating the Option Value of Ashtamudi Estuary in South India: a contingent valuation approach - Anoop, P. and Suryaprakash,S (12th Congress of the European Association of Agricultural Economists - EAAE 2008, 2008)
Ashtamudi estuary of south India provides many direct and indirect use values to the local community in terms of fishing, coconut husk retting, recreation and inland navigation. Nowadays the estuary is facing many threats like pollution, reclamation,injudicious fishing practices etc. At the same time it is having many potential future uses also. So it is imperative to assess the option value of the estuary to appraise the importance to conserve it. Here a contingent valuation method is applied for theassessment. The high option value of the estuary indicates the urgent need of conserving it for the potential future uses